Association of X-ray disease stage with basic patient data, laboratory values and treatment modalities in patients with seropositive rheumatoid arthritis - Alen Omanović; Nejra Mlačo-Vražalić; Akif Mlačo (Medicinski glasnik, 2024)
Aim: To investigate whether the radiographic progression of rheumatoid arthritis (RA) correlates with inflammatory markers and other laboratory values, and its association with treatment modalities. Methods: This observational study included 125 patients with seropositive RA. Data were obtained from patients’ medical records from the year of 2022. Inclusion criteria were patients with seropositive RA who had attended follow-up with a rheumatologist. Basic patient data were collected: gender, age, duration of RA, hospital admission, systolic and diastolic blood pressure, and X-ray stage of RA. Stages of RA are defined by the American College of Rheumatology and they ranged from stage 1, which represents no de-structive changes on X-ray, up to stage 4 where bony or fibrous ankylosis is present. Results: There were no differences in X-ray stages of RA between genders. Patients with a higher X-ray stage were younger and had a longer duration of illness. Patients in stages III and IV had higher systolic blood pressure (BP), patients in stage IV had higher diastolic BP. Erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) were higher in X-ray stages II-IV compared to stage I. The patients treated with methotrexate had higher radio-graphic stages. Conclusion: X-ray changes can be associated with CRP and ESR levels, since structural damage is related to RA disease activity and functional disability. The use of newer treatment modalities may be required to stop the radiographic progression of RA.
Keywords: inflammation; radi-ology; rheumatolo-gy